'The World Must be Romanticised ...': The (Environmental) Ethical Implications of Schelling's Organic Worldview. (1st August 2005) - Miller, Elaine P.
Abstract : This essay addresses the implications of German Idealism and Romanticism, and in particular the philosophy of Schelling as it is informed by Kant and Goethe, for contemporary environmental philosophy. Schelling's philosophy posits a nature imbued with freedom which gives rise to human beings, which means that any ethics, insofar as ethics is predicated upon freedom, will be an 'environmental ethic'. At the same time, Schelling's organismic view of nature is distinctive in positing a fundamental gap between nature and human beings. Without this absolute alterity, there could be no real ethical relationship between human beings and nature. I conclude by briefly gesturing toward Schelling's role in the development of an ethics of alterity (which I apply to environmental ethics) in continental philosophy through Heidegger, Derrida, and Levinas.